Peran Baznas dalam Meningkatkan Kesejahteraan Masyarakat Miskin Melalui Zakat Produktif di Kabupaten Kampar - Rinaldi, Rinaldi (Journal of Economics and Business Research (JUEBIR), 2025)
This study analyzes the role of productive zakat distributed by BAZNAS in improving the welfare of the poor in Kampar Regency using NVivo analysis. The findings indicate that productive zakat significantly impacts security, freedom, self-identity, and welfare. Beneficiaries experience more stable income, greater autonomy in managing businesses, enhanced confidence, and improved family quality of life. Beyond the economic aspect, productive zakat also strengthens social and psychological dimensions, thereby reducing dependency, enhancing dignity, and fostering sustainable self-reliance among the poor.